Chapter 11 The Triad of Uncertainty The Interaction Between Scientists and Politicians - Malnes, Raino (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter sheds light on interaction (samhandling) between scientists and politicians. What happens when the latter gives the former a role in an effort to ensure that society is not exposed to an unforeseen calamity? The chapter has two objectives - one conceptual and one pertaining to the analysis of public policy in a particular context. First, distinctions are drawn between three dimensions of uncertainty about the consequences of action. The aim is to create a clearer understanding of what is meant by assertions that policy is made under conditions of uncertainty. Secondly, the political implications of uncertainty are charted with particular reference to the choice of climate policy. The analysis targets the way the Intergovernmental Panel on Climate Change (IPCC) has handled the task of publicizing the effect that anthropogenic emissions of greenhouse gases have on the atmosphere. The conclusion is that the IPCC's communication with politicians and the public has contributed to, rather than ameliorated, the problem of uncertainty that stands in the way of resolute political action."